K
Khách

Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.

\(H=1+2+2^2+2^3+2^4+....+2^{2009}\)

\(\Rightarrow2H-H=\left(2+2^2+2^3....+2^{2010}\right)-\left(1+2+2^2+...+2^{2009}\right)\)

\(\Rightarrow H=2^{2010}-1=K\)

3 tháng 8 2016

2.H = 2 + 22 + 23 + ... + 22010

2.H - H = (2 + 22 + 23 + ... + 22010) - (1 + 2 + 22 + ... + 22009)

H = 22010 - 1 = k

28 tháng 5 2016

Câu F có lộn đề ko bạn

1.1/3+1/6+1/10+...+2/x.(x+1)=2007/2009

=>2/6+2/12+2/20+...+2/x.(x+1)=2007/2009

=>1/2-1/3+1/3-1/4+1/4-1/5+...+1/x-1/(x+1)=2007/2009:2

=>1/2-1/(x+1)=2007/4018

=>1/(x+1)=1/2-2007/4018

=>1/x+1=1/2009

=>x+1=2009

=>x=2009-2008

=>x=1

vậy x=1

 

28 tháng 4 2018

làm đúng rồi nhưng phần: 

x+1=2009

x=2009-1

x=2008

mà bạn

15 tháng 4 2019

\(\Rightarrow\)2K=\(1+\frac{1}{2}+\frac{1}{2^2}+....+\frac{1}{2^{19}}\)\(\Rightarrow2K-k=k=1+\frac{1}{2}+\frac{1}{2^2}+...+\frac{1}{2^{19}}-k\)

\(\Rightarrow k=1-\frac{1}{2^{20}}< 1\)

\(\Rightarrow k< H\)

Vậy......